Ethnoecology of The Slamet Mountain Slope Community (SMSC) in Paguyangan District, Brebes Regency, Central Java - Nabela Fikriyya; Hendra Helmanto; Rizmoon Nurul Zukarnaen; Nisyawati Nisyawati; Marina Silalahi (Jurnal Biodjati, 2022)
The local communities have local knowledge in utilizing and managing landscape units. The threat of modernization has led to the degradation of local knowledge, including the Javanese community on Mt. Slamet. This study aimed to analyze the plant diversity characteristics of landscape units and determine the important value of landscape units and plant species used by the community. This research was conducted in the Ragatunjung, Cipetung, and Pandansari village, Paguyangan District, Brebes Regency, Central Java. Semi-structured interviews collected Ethnoecological data with eight key informants and 83 respondents selected by purposive sampling and snowball sampling. Data on the level of landscape utilization were analyzed using the Local User's Value Index (LUVI). The community recognizes nine types of landscape units, such as perawisan (yard), wanah (production forest), Majegan (gardens), Sabin (rice fields), Kubang buyut (protected forest plan), tea plantations, Telaga Ranjeng Nature Reserve, Tanah Bengkok and tuk (water sources). Wanah was the most important landscape unit in the community in Ragatunjung (31.27), Cipetung (53.55), and Pandansari (28.17). Oryza sativa had the highest importance value in Sabin (22) and wanah (12) of Ragatunjung. In contrast, Syzygium aromaticum had the highest in Majegan (6.68). Brassica oleracea has the highest importance value in the two landscape units of Cipetung, namely, Majegan (4.20) and settlements (3.5), while in the wanah is Zea mays (11.38). Solanum tuberosum had the highest value in each landscape unit in Pandansari, both in wanah (10.33), Majegan (6.80), and Protection Forest Plan (PFP) (4.13). Categorizing landscapes and their utilization by maintaining certain landscapes, such as the Telaga Ranjeng Nature Reserve and Kubang buyut, directly impact the sustainability and integrity of ecosystems and natural resources in and around the area.